Invasive and in situ lesions of squamous cell carcinoma are independent factors for postoperative surgical‐site infection after outpatient skin tumors surgery: A retrospective study of 512 patients. Issue 4 (9th February 2021) - Nakamura, Yoshiyuki; Sasaki, Katsuhito; Ishizuki, Shoichiro; Inoue, Sae; Okune, Mari; Kubota, Noriko; Okiyama, Naoko; Furuta, Junichi; Fujisawa, Yasuhiro
Abstract: Surgical‐site infection (SSI) is one of the major postoperative complications in surgery, which can cause significant morbidity. However, factors associated with SSI in dermatological surgery are not well understood. Here, we retrospectively investigated 512 patients who underwent outpatient surgery for skin tumors at the University of Tsukuba Hospital to analyze factors associated with postoperative SSI. The overall incidence of SSI was 28 (5.5%). Univariate logistic regression analysis revealed that SSI was significantly associated with invasive squamous cell carcinoma (iSCC), Bowen's disease (BD), actinic keratosis (AK), longer diameter of defects, presence of ulcer, reconstruction with full‐thickness skin graft and local skin flaps, medical history of diabetes mellitus, and use of immunosuppressive agents. However, in the multivariate analysis only iSCC, BD, and AK retained significance. The frequencies of SSI in iSCC, BD, and AK were 22% (13/58 patients), 15.6% (5/32), and 25% (2/8), respectively; however, the frequency of other non‐SCC tumors was only 1.9% (8/414). χ 2 ‐Tests revealed that the frequency of SSI in iSCC, BD, and AK were all significantly higher than in non‐SCC tumors, with the frequencies being more than eight times higher. These results suggest that invasive and in situ lesions of SCC are independent risk factors of SSI development after outpatient skin surgery.